2017
DOI: 10.17349/jmc117317
|View full text |Cite
|
Sign up to set email alerts
|

Drone Journalism: Generating Immersive Experiences

Abstract: During the past, few years, the journalistic community were expecting the time that the use of drones in their day to day job would be a common place. Due to ethics and privacy considerations, as well as regulation restrictions that are applied in most countries, this moment has yet to come. However, the use of drones during conflicts, civil unrests and environmental disasters is a proof that drone-generated content can be a valuable tool to tell a story. Their cost effectiveness and data gathering capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 6 publications
0
13
1
5
Order By: Relevance
“…This image of a more reserved attitude among photojournalists contrasts with research exploring the creativity of early adopters (Belair-Gagnon et al, 2017) and other studies which have positioned drones as a disruptive innovation (Ferguson & Greer, 2019;Gynnild & Uskali, 2018) The results are more in line with the more critical approaches that have highlighted limiting factors in the actual use of drones (Barrero, 2018;Ntalakas et al, 2017), as well the results of content analysis of drone journalism, which found that in the majority of the cases, drone footage was used to establish context (Adams, 2019).…”
Section: Resultscontrasting
confidence: 58%
“…This image of a more reserved attitude among photojournalists contrasts with research exploring the creativity of early adopters (Belair-Gagnon et al, 2017) and other studies which have positioned drones as a disruptive innovation (Ferguson & Greer, 2019;Gynnild & Uskali, 2018) The results are more in line with the more critical approaches that have highlighted limiting factors in the actual use of drones (Barrero, 2018;Ntalakas et al, 2017), as well the results of content analysis of drone journalism, which found that in the majority of the cases, drone footage was used to establish context (Adams, 2019).…”
Section: Resultscontrasting
confidence: 58%
“…Amongst others, the media landscape has been already transformed into a new digital experience (and continues to elaborate constantly), bringing modern tools forward that accelerate mediated communication, i.e., thru easy multimedia production and sharing, sophisticated content documentation and management, semantic interpretation and conceptualization of data (and meta-data), information recognition, and retrieval. While these fresh services offer innumerous capabilities in both ends of media production and consumption, they also raise multiple concerns, uncertainties, and hesitations regarding how to exploit the released capacities without being exposed to ethical, privacy, and security risks or dangerous pathways [1][2][3][4][5]. Clearly, the frequently immature and unstable character of the lately launched assets/facilities, along with the lack of related operational knowledge and experience, are listed among the foremost causes that deteriorate fast adoption and utilization of pioneering machinery [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Both scholars and journalists emphasized this role of drone technology in community contexts: Gynnild and Uskali (2018, p. 12) describe drone technology in journalism as a “disruptive innovation,” which will soon be “a natural and ubiquitous part of our lives.” (see also Goldberg et al, 2013; Gynnild, 2014); africanDRONE believes that the flying robots “give citizens powerful new ways to understand their world better and to improve public accountability,” 1 and Rafsky (2017) considers Unmanned Aerial Vehicles (UAVs) employment in “documentation, storytelling and advocacy purposes” as an “important lessons as drones increasingly become part of the documentation toolkit” for journalists and activists. Ntalakas et al (2017, p. 187) sustain that “the use of drones during conflicts, civil unrest and environmental disasters is a proof that drone-generated content can be a valuable tool to tell a story”; Ben Kreimer (2018, p. 92) observes that drones and the data they produce as journalistic tools “enlighten and reveal stories by taking audiences into inaccessible spaces, capturing surprising visuals, and opening up new perspectives.”…”
Section: Media Activism Journalism and The Domestication Of Drone Tmentioning
confidence: 99%